Challenges in oral drug delivery in patients with esophageal dysphagia. (3rd May 2016) - Kappelle, Wouter F. W.; Siersema, Peter D.; Bogte, Auke; Vleggaar, Frank P.
ABSTRACT: Introduction: Esophageal dysphagia is a commonly reported symptom with various benign and malignant causes. Esophageal dysphagia can impede intake of oral medication, which often poses a major challenge for both patients and physicians. The best way to address this challenge depends of the cause of dysphagia. Areas covered: The pathophysiology of esophageal dysphagia is discussed, diagnostic tools to determine its cause are reviewed and recent developments in the treatment of esophageal dysphagia are discussed. Alternative options to administer medication in dysphagia are discussed and the appropriateness of them reviewed. Expert opinion: Two ways can be followed to allow medication intake in patients with esophageal dysphagia, i.e. altering medication or resolving dysphagia. The latter is generally preferred, since esophageal dysphagia rarely only impedes medication intake. Esophageal resection is possible in more advanced esophageal cancer stages due to advances in neo-adjuvant therapy. Due to recent improvements in intraluminal radiotherapy, it can be expected that this will be the primary treatment in a palliative setting. Temporary self-expandable metal stent placement is a promising new alternative for bougienage in difficult-to-treat benign strictures.